Microbial Fuel Cell and its Efficiency in Treating Wastewater - a Novel Technique for Wastewater Treatment - Antony Fantin, B; Ramesh, S; S.Sudarsan, J; Vanamoorthy Kumaran, P (International Journal of Engineering and Technology, 2018)
Due to depletion of coal and other natural fuel there is an urgent need to find eco-friendly and workable technology for alternate energy. Microbial fuel cells is considered as assuringmethod to extract energy from various sources of wastewater and to generate electricity. But, due to practical limits, MFCs are still unsuitable to meet high power demands. Since wastewater contains several contaminants including organic substances, therefore, generation of electric energy from wastewater using MFC can offer an alternate solution for electricity issue as well as to reduce environmental pollution. Microbial fuel cells harvest electrical energy from wastewater with the help of microorganisms present within the wastewater. The energy confined in organic matter converted in to useful electric current. In Microbial Fuel Cell electrons from the microorganisms transfer from a reduced electron donor to an electron acceptor at a higher electrochemical potential. The study highlights that wastewater with high organic content found to be more effective and it also gives good energy production. If the same concept implemented in large scale it can help in achieving sustainable development and it helps in achieving 3R formula in the process of wastewater treatment.
Keywords: Microbial Fuel Cell (MFC); Microorganisms; Wastewater; Energy production; Organic content; 3R formula.